Features of T lymphocyte subpopulation profile in patients with ankylosing spondylitis undergoing genetically engineered biological therapy - A. A. Savchenko; O. D. Gritsenko; A. G. Borisov; I. V. Kudryavtsev; M. K. Serebriakova; A. A. Masterova; P. A. Shesternya (Медицинская иммунология, 2021)
The aim of current study was to compare profiles of T cell subsets in the patients with ankylosing spondylitis (AS) who received different modes of genetically engineered biological therapy (GEBT). The research involved 58 patients aged 20 to 58 years diagnosed with AS and treated with anti-TNFα and antiIL-17 drugs, as well as those receiving common anti-inflammatory therapy. The AS diagnostics was based on the modified New York criteria. Disease activity was assessed by means of nomenclature approved by the Assessment of Spondyloarthritis International Society and Outcome Measures in Rheumatology. 45 healthy people aged 18 to 57 were included into the control group. Peripheral blood T cell subsets were analysed by multicolor flow cytometry. It was found that the T lymphocyte subpopulation profiles in AS patients showed significant differences depending on the therapy type. First, T lymphocyte counts were decreased in AS patients receiving traditional anti-inflammatory therapy, whereas relative numbers of T cells with high levels of effector potential and cytokine secretion were increased. Negative correlations between the levels of effector memory and pre-effector cytotoxic T cells and other laboratory and clinical indexes of inflammatory activity in AS may reflect lower efficiency of traditional therapy. Next, the levels of main T cell subsets in AS patients during antiIL-17 therapy fully corresponded to the control values. However, based on numerous correlations between immunological and clinical laboratory parameters, it was concluded that anti-IL-17 therapy had an inhibitory effect on the joint inflammation activity, while the state of T cell subsets was mainly dependent on standard anti-inflammatory therapy. The most pronounced changes in T cell subsets were found in AS patients during anti-TNFα therapy was associated with decreased effector potential of Th cells and cytotoxic T lymphocytes. At the same time, the lowest frequency of extraskeletal manifestations was found in AS patients treated with anti-TNFα drugs. Finally, the higher efficiency of GEBT, compared with conventional methods of therapy, is determined by the effects upon immune targets of AS pathogenesis which manifested, e.g., by changes in the T lymphocyte subpopulation profile. Moreover, usage of anti-TNFα versus anti-IL-17 inhibitors was associated with greater effect upon phenotypic profile of T cells.